Selective CB2 inverse agonist JTE907 drives T cell differentiation towards a Treg cell phenotype and ameliorates inflammation in a mouse model of inflammatory bowel disease. (March 2019) - Gentili, Marco; Ronchetti, Simona; Ricci, Erika; Di Paola, Rosanna; Gugliandolo, Enrico; Cuzzocrea, Salvatore; Bereshchenko, Oxana; Migliorati, Graziella; Riccardi, Carlo
Graphical abstract: Abstract: Cannabinoids are known to possess anti-inflammatory and immunomodulatory properties, but the mechanisms involved are not fully understood. CB2 is the cannabinoid receptor that is expressed primarily on hematopoietic cells and mediates the immunoregulatory functions of cannabinoids. In order to study the effect of JTE907, a selective/inverse agonist of CB2 with anti-inflammatory properties, on the differentiation of T cell subtypes, we used an in vitro system of Th lineage-specific differentiation of naïve CD4 + T lymphocytes isolated from the mouse spleen. The results indicate that JTE907 was able to induce the differentiation of Th0 cells into the Treg cell phenotype, which was characterized by the expression of FoxP3, TGF-β and IL-10. P38 phosphorylation and STAT5A activation were found to mediate the signaling pathway triggered by JTE907 via the CB2 receptor in Th0 lymphocytes. In mice with DNBS-induced colitis, JTE907 treatment was able to induce an increase in the number of CD4 + CD25 + FoxP3 + cells in the lamina propria after 24 h of disease onset and reduce disease severity after 48 h. Further, longer JTE907 treatment resulted in less severe colitis even when administered orally, resulting in less body weight loss, reduction of the disease score, prevention of NF-κB activation, and reduction of the expression of adhesion molecules. Collectively, the results of this study indicate that specific signals delivered through the CB2 receptor can drive the immune response towards the Treg cell phenotype. Thus, ligands such as JTE907 may have use as potential therapeutic agents in autoimmune and inflammatory diseases.